Asymmetric synthesis of (R)-(-)-baclofen via asymmetric dihydroxylation - Thakur, V. V.; Paraskar, A. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
A short and efficient asymmetric synthesis of (R)-(-)-baclofen, a selective GABA(B) agonist has been described with an overall yield of 14% and 85% ee. The Os-catalyzed Sharpless asymmetric dihydroxylation of alpha,beta-unsaturated olefin constitutes the key step in introducing stereogenic centers into the molecule.
Keywords: asymmetric dihydroxylation; baclofen; cyclic sulfate; gamma-aminobutyric acid; Parkinsons' disease